Tigecycline Pharmacokinetic and Pharmacodynamic Profile in Patients with Chronic Obstructive Pulmonary Disease Exacerbation - Maria Kipourou; Olga Begou; Katerina Manika; Georgios Ismailos; Paschalina Kontou; Georgia Pitsiou; Helen Gika; Ioannis Kioumis (MDPI AG, 2023)
Background: We aimed to evaluate the pharmacokinetic profile of tigecycline in plasma and its penetration to sputum in moderately ill patients with an infectious acute exacerbation of chronic obstructive pulmonary disease (COPD). Methods: Eleven patients hospitalized with acute respiratory failure due to an acute COPD exacerbation with clinical evidence of an infectious cause received tigecycline 50 mg twice daily after an initial loading dose of 100 mg. Blood and sputum samples were collected at steady state after dose seven. Results: In plasma, mean Cmax pl was 975.95 ± 490.36 ng/mL and mean Cmin pl was 214.48 ±140.62 ng/mL. In sputum, mean Cmax sp was 641.91 ± 253.07 ng/mL and mean Cmin sp was 308.06 ± 61.7 ng/mL. In plasma, mean AUC 0-12 pl was 3765.89 ± 1862.23 ng*h/mL, while in sputum mean AUC 0-12 sp was 4023.27 ± 793.37 ng*h/mL. The mean penetration ratio for the 10/11 patients was 1.65 ± 1.35. The mean Free AUC0-24 pl/MIC ratio for Streptococcus pneumoniae and Haemophilus influenzae was 25.10 ± 12.42 and 6.02 ± 2.97, respectively. Conclusions: Our findings support the clinical effectiveness of tigecycline against commonly causative bacteria in COPD exacerbations and highlight its sufficient lung penetration in pulmonary infections of moderate severity.